Amphiphilic block co-polymer and silica reinforced epoxy composite with excellent toughness and delamination resistance for durable electronic packaging application. (6th April 2022) - Lee, Minkyu; Paria, Sarbaranjan; Mondal, Subhadip; Lee, Gi-Bbeum; Shin, Beomsu; Kim, Suhyun; Park, Sungjune; Nah, Changwoon
Abstract: Addition of silica brings a significant improvement in flexural strength and toughness of epoxy thermoset yet; these properties suffers a huge change when an amphiphilic BCP and silica have been used together. Here, a triblock BCP, poly(methyl methacrylate)-b-poly(butyl acrylate)-b-poly(methyl methacrylate) (PMMA-b-PBuA-b-PMMA), is employed in silica-epoxy system to study its structural and mechanical properties. On copolymerization with poly(dimethyl acrylamide) (PDMA), with either PMMA block, both flexural strength and toughness enhanced manifold and found to be of 152 MPa and 0.79 J, respectively, at 83 wt% silica and 1.5 wt% PDMA copolymerized BCP loading. Moreover, it exhibits best delamination resistance index of 74 which displays its superiority in practical applications over other composites. The miscibility of PMMA-PDMA chain with epoxy, its interaction with silica particles and existence of wormlike structure of BCPs in composite simultaneously play the key role for high flexural strength, toughness and delamination resistance of the composite. Graphical abstract: Image 1 Highlights: ➢ Amphiphilic BCP and silica used for epoxy reinforcement ➢ Flexural strength and toughness of 152 MPa and 0.79 J ➢ Delamination resistance index of 74 ➢ Wormlike structure of BCPs